Hearts and Hahas of the Public: Exploring How Protest Frames and Sentiment Influence Emotional Emoji Engagement with Facebook News Posts. (10th September 2021) - Kilgo, Danielle K.; Harlow, Summer
ABSTRACT: The protest paradigm, which describes the unequitable reciprocity of the media-social movement relationship, creates a double-bind for social movements. Mainstream news media in the United States emphasize emotion, drama, and irrationality while excluding the grievances, agendas, and substance behind a protest, contributing to negative narratives that can hinder public support for a movement. This analysis of Facebook news posts of protests by mainstream U.S. news organizations contributes to our understanding of how social media's engagement affordances work in cohort with journalists' use of emotional appeals to legitimize some protests and delegitimize others. Results show posts encourage the mobilization of some protests more than others, and media frames and emotional linguistic devices might contribute to a spectrum of delegitimizing framing effects. Legitimizing features significantly decrease emotional reactions from audiences, leading to more neutral but potentially less engaging audience reception and response. Findings advance our understanding protest paradigm framing outcomes.